Eugène Ionesco, 1942-1944 : Political and Cultural Transfers between Romania and France - Julia Elsky (Diasporas: Circulations, Migrations, Histoire)
This article discusses the cultural and political exchanges organized by the playwright Eugène Ionesco when he worked for the Romanian Delegation to Vichy between 1942 and 1944. Drawing on unstudied archives of the Romanian Ministry of Propaganda, it analyzes exchanges between French and Romanian professors and students, as well as the role Ionesco played in seeking faculty positions for Romanian professors in France. Ionesco’s reports reveal a cultural policy with two goals: promoting Franco-Romanian relations and combatting Hungarian propaganda in France, often through literary, cultural, academic, and linguistic exchanges. This article examines the notion of circulation in cultural diplomacy and its political stakes during the Second World War.